Bacterioscopic method of the snails’ meat freshness determination - Zabarna, I. V. (НУБіП України, 2019)
The aim of the study was to improve and determine the degree of freshness of meat of snails of Helix genus after different technological processing by bacterioscopic method. Since there is no data in the modern scientific literature about the determination of indicators of safety and quality of meat of snails, in particular the freshness of meat of different species and different technological processes by bacterioscopic method, therefore the problem is relevant. The meat of snails of genus Helix has been used for the study, subspecies: Helix pomatia, Helix aspersa maxima and Helix aspersa muller. 30 samples of meat of snails of each species, bred in a snail farm of the Kyiv region were selected for the study. The research was conducted in the winter, when the snails were in anabiosis condi􀆟on. The meat of snails was investigated after various technological processing: live, chilled and cooked and frozen. According to the results of the study, it was found that the meat of live snails was fresh for 2 days; doubtful freshness – from 3 days to 5 days; stale – in 7 days; freshly chilled meat of snails was fresh in 2 days including; doubtful freshness – from 3 to 6 days; stale – in 7 and 8 days; and coocked and chilled snails’ meat was fresh after the storage for 6 months at a temperature of minus 18 °С. These data are stable and reliable, therefore, these indicators can be used in assessing the safety of snail meat under different processing conditions and aster different storage periods.
Keywords: microorganisms; Helix pomatia; Helix aspersa maxima; Helix aspersa muller; snails’ meat; bacterioscopic performance